Vaccine containing immunologic adjuvants with a wide range of activity to provide protection against COVID-19 - Berhanu, Mulugeta (My University, 2021)
COVID-19 is a devastating viral disease which can be prevented by vaccination. Immunologic adjuvants are key to develop an effective vaccines against infectious diseases in human and non-human primates. Vaccines containing an appropriate adjuvants are crucial for the prevention of various infectious diseases which are the biggest threats to human and animal health. This paper proposes a wide spectrum immunologic adjuvant for vaccine development against COVID-19 which is the current global problem. It has been reported that a wide range of immune cells are involved in the body’s response to SARS CoV2 infection. Therefore, vaccine with a wide-spectrum immunologic adjuvant can be used to provide protection against COVID-19. Lack of adjuvants that can induce the required immune responses is a serious impediment to vaccine development against this devastating virus. The approved adjuvants such as aluminum salts and MF59 exhibit a narrow range of activity. In an attempt to solve this problem, it is crucial to develop new adjuvants which can trigger a wide range of immune cells.
Keywords: Adjuvants for COVID-19vaccines; Aluminumsalts; COVID-19; Immunologic adjuvants; MF-59; SARS CoV2; Vaccine development against COVID-19; Vaccine with a wide-spectrum immunologic adjuvant